2017
DOI: 10.1016/j.meatsci.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Selection for intramuscular fat and lean meat yield will improve the bloomed colour of Australian lamb loin meat

Abstract: The colour of bloomed m. longissimus was measured 24h post slaughter for 8165 lamb carcasses produced over 5years across 8 sites in Australia. Intramuscular fat across a 2 to 8% range and shortloin fat weight were positively associated with meat lightness (L*), redness (a*), yellowness (b*), hue and chroma (P<0.01). Shortloin muscle weight was negatively associated with these meat colour parameters (P<0.01), although this was largely accounted for by correlated changes in intramuscular fat (P<0.01). The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…The genetic correlations for live weight with the other meat quality traits tended to be negligible, which was consistent with reported genetic correlations for meat color (Fogarty et al, 2003;Greeff et al, 2008;Mortimer et al, 2010;Brito et al, 2015Brito et al, , 2017, IMF (Brien et al, 2013, an earlier multibreed sampling of the IN progeny; Mortimer et al, 2010), and shear force (Brien et al 2013;Brito et al, 2015Brito et al, , 2017. Also, no effect has been observed of sire pwWT EBV on meat color (Calnan et al, 2017), except L* (Hopkins et al, 2005), or IMF (Hopkins et al, 2007a;Pannier et al, 2014c;Anderson et al, 2015) and shear force (Hopkins et al, 2005;Allingham et al, 2006). However, low-positive genetic correlation between shear force and live weight at later ages may exist as shown by the present study and reported by Mortimer et al (2010).…”
Section: Live Weight Traitssupporting
confidence: 82%
See 1 more Smart Citation
“…The genetic correlations for live weight with the other meat quality traits tended to be negligible, which was consistent with reported genetic correlations for meat color (Fogarty et al, 2003;Greeff et al, 2008;Mortimer et al, 2010;Brito et al, 2015Brito et al, , 2017, IMF (Brien et al, 2013, an earlier multibreed sampling of the IN progeny; Mortimer et al, 2010), and shear force (Brien et al 2013;Brito et al, 2015Brito et al, , 2017. Also, no effect has been observed of sire pwWT EBV on meat color (Calnan et al, 2017), except L* (Hopkins et al, 2005), or IMF (Hopkins et al, 2007a;Pannier et al, 2014c;Anderson et al, 2015) and shear force (Hopkins et al, 2005;Allingham et al, 2006). However, low-positive genetic correlation between shear force and live weight at later ages may exist as shown by the present study and reported by Mortimer et al (2010).…”
Section: Live Weight Traitssupporting
confidence: 82%
“…There tended to be also generally low to moderate positive genetic correlations for FATUS and EMDUS with Myo (0.25 ± 0.24 to 0.43 ± 0.14) and cfa* (−0.06 ± 0.36 to 0.57 ± 0.35), and negative with cfL* (−0.05 ± 0.26 to −0.52 ± 0.31). Genetic correlation estimates for these traits from other studies are variable (Greeff et al, 2008;Mortimer et al, 2010;Brito et al, 2015Brito et al, , 2017, with sire EBV for the ultrasound traits having no (Gardner et al, 2006) to a small positive (Kelman et al, 2014) effect on Myo and no (Hopkins et al 2005(Hopkins et al , 2007b to small effects on the meat color traits (positive of muscle depth on redness, and negative of fat depth on redness and lightness in Merinos; Calnan et al, 2017). However, our results suggest that selection to increase FATUS and EMDUS in Merinos may result in increased Myo and meat redness (cfa*), but decreased meat brightness (cfL*), although any correlated changes would be small.…”
Section: Ultrasound and Meat Quality Traitsmentioning
confidence: 99%
“…A large number of studies have reported quantitative trait loci (QTLs) that affect different fat deposition sites in different strains and experimental populations. Theoretically, genes involved in lipid metabolism have potential regulatory effects on intramuscular fat content 22 . However, there are few reports on intramuscular fat related molecular markers (DNA maker) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies with lamb have shown that carcass intramuscular fat deposition and FA composition account for eating quality variation [198,199]. Consumption of lamb IMF is important to humans since it helps with the delivery and absorption of fat-soluble vitamins, and exerts positive effects on immune response [200] as exemplified by Calder's work [58] demonstrating the relationship between fatty acid composition of immune cells and their function. Marbling score to date remains one of the most important traits and reason why carcass evaluation is carried out in the abattoir [201].…”
Section: Meat Eating Qualitymentioning
confidence: 99%